Genistein supplementation modulates the intestinal microbiota–liver–lumbar muscle metabolic axis in DLY commercial pigs without concomitant changes in growth performance - Du, Yong; Yang, Yiting; Wang, Yan; Wu, Yuanyuan; Liu, Chengming; Hao, Ziling; Yan, Zhijuan; Mao, Junxiang; Wen, Jiaqi; Zhao, Ye; Niu, Lili; Zhou, Xiaofeng; et al. (Frontiers in Microbiology, 2025)
Genistein is widely found in leguminous plants. As an isoflavone, it has functions similar to mammalian estrogen and has effects on many aspects such as animal carcass performance, intestinal flora composition and physiological metabolism. This study aimed to investigate the effects of genistein supplementation on the carcass performance of commercial pigs via intestinal microorganisms, liver and lumbar muscle metabolites. Sixteen DLY commercial pigs were divided into two groups: a fed group receiving a diet supplemented with 160 mg/kg genistein and a control group without supplementation; the intervention lasted about 74 days. The bacterial genome of the 16SrRNA V3–V4 region was sequenced to observe the diversity and composition changes of microorganisms in the feces of the fed group and the control group. At the same time, the differential metabolites and metabolic pathways of the liver and lumbar muscle tissues of the fed group and the control group were jointly analyzed. The results of the study showed that the addition of genistein to feed can increase the relative abundance of Firmicutes, reduce the relative abundance of Bacteroidetes, and generally improve the relative abundance and diversity of intestinal flora. Combined analysis of intestinal microorganisms and liver and lumbar muscle metabolomes revealed that genistein supplementation can enhance the Aminoacyl-tRNA biosynthesis, Pentose phosphate pathway, and Pyrimidine metabolism through the gut-liver axis, promote the synthesis of proteins and nucleic acids, and maintain whole-body carbon–nitrogen metabolic homeostasis. It can also enhance Fructose and mannose metabolism, Amino sugar and nucleotide sugar metabolism, and Pentose phosphate pathway through the gut-muscle axis, promote the metabolism of carbohydrates such as amino sugars and fructose, provide energy, and maintain energy balance in the body. Correlation analysis showed that although there were no significant differences in host phenotypic values, genistein supplementation may affect host phenotypic values by changing the relative abundance of bacterial genera associated with the phenotype.